Peran Inovasi Dan Kompetensi Sumber Daya Manusia Terhadap Persaingan UMKM Di Kabupaten Bengkayang - Hilarianty, Hilarianty; Maisela, Maisela (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2024)
This research aims to determine the role of innovation and human resource capabilities in competition for micro, small and medium enterprises (MSMEs) in Bengkayang Regency. In the era of globalization and increasingly fierce competition, MSMEs face challenges to continue to improve the quality of their talents and innovate. This research uses a qualitative approach by collecting data through observation and interviews. The research results show that innovation and HR capabilities have a significant influence on competition in MSMEs. Product, process and marketing innovations, as well as increasing human resource capabilities in terms of knowledge, skills and attitudes have been proven to be able to increase the competitiveness of MSMEs in Bengkayang Regency. This research provides important insights for developing strategies and policies that can support innovation and increase the human resource capacity of MSMEs in Bengkayang Regency so that they can be more competitive in global competition